Understanding the Social Functions of Nonsuicidal Self-Injury in Community Adolescents - Brooks, Andrea R. (Canadian Journal of Counselling and Psychotherapy, 2015)
The objective of this article is to provide clinicians with an overview of various social functions of nonsuicidal self-injury as they relate to recent cross-cultural literature, in order to ultimately inform effective treatment planning. Evidence is presented supporting Nock’s (2008) social theory of nonsuicidal self-injury, indicating that self-injury acts as a means of communication, often relating to unreceptive environments or through skill deficits. Further evidence is presented suggesting self-injury acts as a way of avoiding undesirable tasks or increasing group belonging and closeness in relationships. Although the media may influence self-injury, the relationship is complex and remains unclear. Given the above findings, practitioners should focus on addressing skill deficits, including family members in treatment, investigating the role of the Internet in relation to self-harm, and developing an appropriate professional response in order to reduce contagion.